‘Everybody Knows that the Prisoner is Going Nowhere’: Parole Board Members’ Views about Dangerous and Severe Personality Disorder in England and Wales - Trebilcock, Julie; Weaver, Tim (International Journal of Criminology and Sociology, 2012)
The Dangerous Severe Personality Disorder (DSPD) Programme has been a controversial initiative in England and Wales. First introduced in 1999, DSPD became a highly contested operational as opposed to diagnostic term, used to define a population convicted of violent offences who were admitted for treatment within one of four high security units established for men. The aim of this paper is to explore the outcomes of Parole Board (PB) reviews with DSPD prisoners and investigate PB members’ views about DSPD. Nearly all PB members observed that the high security location of the DSPD units was more influential to their decision-making than the label of DSPD. PB members highlighted their expectation that DSPD prisoners make a journey through different levels of security before release is an appropriate consideration. A key finding was that admission to DSPD services could be seen to have disrupted a prisoner’s progression and challenged PB members’ conceptions of the appropriate (and likely) future progression pathways available to prisoners. These findings have implications not only for the development of the new offender personality disorder pathway in England and Wales but also for other jurisdictions seeking to respond to the long-standing question of how to respond to high risk offenders with personality disorder.